7. b) (+5,3) + (−10) + (+3,1) + (+4,7);
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(+5,3)+(-10)+(+3,1)+(+4,7)
\(=5,3-10+3,1+4,7\)
\(=\left(5,3+4,7\right)-10+3,1\)
\(=10-10+3,1\)
\(=3,1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,(-5,3)+(-0,7)+5,3
=(-5,3+-0,7)+5,3
=-6+5,3
=-0,7
b, 5,3+(-10)+3,1+4,7
=(5,3+4,7)+(-10)+3,1
=10+(-)+3,1
=0+3,1
=3,1
c, (-4,1)+(-13,7)+(3,1)+(-5,9)+(-6,3)
=(-4,1+-5,9)+(-13,7+-6,3)+-3,1
=(-10). +(-20). +-3,1
=(-30). +-3,1
=33,1
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =5,3-0,7-5,3=-0,7
b: =5,3-10+3,1+4,7
=10-10+3,1=3,1
c: =9+3,6-4,1+1,3
=9+0,8=9,8
d: =21/47+26/47+1/5+4/5
=1+1
=2
e: =3/8(58/3-33/3)
=3/8*25/3
=25/8
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.5,3.4,7+\left(-17\right).5,3-5,9\)
\(=5,3.\left[4,7+\left(-17\right)\right]-5,9\)
\(=5,3.\left(-12,3\right)-5,9\)
\(=-65,19-5,9=-71,09\)
\(b.\dfrac{2}{3}+\dfrac{-1}{3}+\dfrac{7}{15}=\dfrac{10}{15}+\dfrac{-5}{15}+\dfrac{7}{15}=\dfrac{12}{15}=\dfrac{4}{5}\)
a) 5,3.4,7+(−1,7).5,3−5,95,3.4,7+(−1,7).5,3−5,9
=5,3.(4,7−1,7)−5,9=5,3.(4,7−1,7)−5,9
=5,3.3−5,9=5,3.3−5,9
=15,9−5,9=10=15,9−5,9=10
b) 23+−13+71532+3−1+157
=2+(−1)3+715=32+(−1)+157
=5+715=1215=45=155+7=1512=54.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(A=\left(3,1-2,5\right)-\left(-2,5+3,1\right)\)
\(A=0,6-0,6\)
\(A=0\)
b) \(B=\left(5,3-2,8\right)-\left(4+5,3\right)\)
\(B=2,5-7,3\)
\(B=-6,8\)
c) \(C=-\left(25-3+2,81\right)+3,251-\left(1-2,8\right)\)
\(C=-24,81+3,251+1,8\)
\(C=-19,759\)
`@` `\text {Ans}`
`\downarrow`
`a,`
`A =(3,1 - 2,5) - (-2,5 + 3,1)`
`= 3,1 - 2,5 + 2,5 - 3,1`
`= (3,1 - 3,1) + (-2,5+2,5)`
`= 0`
Vậy, `A = 0`
`b,`
`B = (5,3 - 2,8) - (4+5,3)`
`= 5,3 - 2,8 - 4 - 5,3`
`= (5,3 - 5,3) + (-2,8-4)`
`= -6,8`
Vậy, `B = -6,8`
`c,`
`C = -(25 - 3 + 2,81) + 3,251 - (1 - 2,8)` `?`
`= -25 + 3 - 2,81 + 3,251 - 1 + 2,8`
`= (-25 + 3 - 1) + (-2,81 + 2,8) + 3,251`
`= -23 - 0,01 + 3,251`
`= -19,759`
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\left(3,1-2,5\right)-\left(-2,5+3,1\right)\)
\(=\left(3,1-2,5\right)-\left(3,1-2,5\right)\)
\(=3,1-2,5-3,1+2,5\)
\(=\left(3,1-3,1\right)+\left(2,5-2,5\right)\)
\(=0+0=0\)
\(B=\left(5,3-2,8\right)-\left(4+5,3\right)\)
\(=5,3-2,8-4-5,3\)
\(=\left(5,3-5,3\right)-\left(2,8+4\right)\)
\(=0-\left(2,8+4\right)\)
\(=-2,8-4=-6,8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2,8+4,7+7,2+5,3\)
\(=\left(2,8+7,2\right)+\left(4,7+5,3\right)\)
\(=10+10=20\)
b) \(12,34+23,87+7,66+23,13\)
\(=\left(12,34+7,66\right)+\left(23,87+23,13\right)\)
\(=20+47=67\)
c) \(45,09+56,73+54,91+43,27\)
\(=\left(45,09+54,91\right)+\left(56,73+43,27\right)\)
\(=100+100=200\)
d)Sửa đề: \(12,23+24,47+31,18+63,3+68,82\)
\(=\left(12,23+24,47+63,3\right)+\left(31,18+68,82\right)\)
\(=100+100=200\)
![](https://rs.olm.vn/images/avt/0.png?1311)
A = (3,1 – 2,5) – (-2,5 + 3,1) = 3,1 – 2,5 + 2,5 – 3,1 = 0
B = (5,3 – 2,8) – (4 + 5,3) = 5,3 – 2,8 – 4 – 5,3
A=(3,1-2,5)-(-2,5+3,1)=3,1-2,5+2,5-3,1=0
B=(5,3-2,8)-(4+5,3)=5,3-2,8-4-5,3=-6,8
![](https://rs.olm.vn/images/avt/0.png?1311)
b,5,3+(-10)+3,1+4,7
=5,3+4,7+(-10)+3,1
=10+(-10)+3,1
=3,1
HT